-3x+7x=5(x+3)-(x+15)

Simple and best practice solution for -3x+7x=5(x+3)-(x+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+7x=5(x+3)-(x+15) equation:


Simplifying
-3x + 7x = 5(x + 3) + -1(x + 15)

Combine like terms: -3x + 7x = 4x
4x = 5(x + 3) + -1(x + 15)

Reorder the terms:
4x = 5(3 + x) + -1(x + 15)
4x = (3 * 5 + x * 5) + -1(x + 15)
4x = (15 + 5x) + -1(x + 15)

Reorder the terms:
4x = 15 + 5x + -1(15 + x)
4x = 15 + 5x + (15 * -1 + x * -1)
4x = 15 + 5x + (-15 + -1x)

Reorder the terms:
4x = 15 + -15 + 5x + -1x

Combine like terms: 15 + -15 = 0
4x = 0 + 5x + -1x
4x = 5x + -1x

Combine like terms: 5x + -1x = 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 9(8c-9)=-81+72c | | -34+z=-59 | | Z+8=9 | | -(-6y-4z-2)= | | x^2-0.6x+0.09= | | 3x=6x-4 | | 10sec^2x-10=7tanx+2 | | 2n/11=-23 | | 14+2/3e=8 | | Z-2=3 | | x+2x+15= | | 5+4e=37 | | 18s^3=50s^3 | | -x+9=24 | | 175000+550T=220650 | | x-40+x=90 | | 5/8=2x+1/8 | | 4k-11=8k+29 | | 35000+1680T=300440 | | 14+w=98 | | 8x^2+36x-13=0 | | y=0.15x^3-5x^2+7 | | 35000+1680T=300400 | | 78=5/9(F-32) | | 35000+1680=300400 | | -5[-5m-10]= | | 2/3*1= | | 2y/5a | | 4x-2+5x+10=2x+4 | | 2+2=c | | 0=25x^2-15x | | 1/3-4k=1/3-5k |

Equations solver categories